SWOT Analysis of the Strategy of Digital Transformation of SMEs - Sihite, Mislan; Suparwata, Dewa Oka; Arafah, Muhammad Nur; Uhai, Sabalius (International Journal of Business, Law, and Education, 2025)
The rapid advancement of digital technologies has significantly influenced business environments, creating both opportunities and challenges for Small and Medium Enterprises (SMEs). This study aims to analyze the strategic position of SMEs in the context of digital transformation using a SWOT framework. A qualitative descriptive research method was employed, utilizing literature review and semi-structured interviews with SME owners and industry practitioners to identify key internal and external factors affecting digital adoption. The findings reveal that SMEs possess strategic strengths such as operational agility, strong customer relationships, and owner-driven decision-making that can support digital transformation initiatives. However, internal weaknesses including limited financial resources, low technological capability, and resistance to organizational change hinder implementation. External opportunities such as growing digital markets, government support programs, and accessible digital tools provide potential pathways for digital acceleration, while threats including cybersecurity risks, regulatory pressures, and increasing digital competition create strategic uncertainties. The study concludes that successful digital transformation for SMEs requires leveraging internal strengths, addressing capability gaps, capitalizing on emerging opportunities, and mitigating external risks through strategic planning. These insights provide valuable implications for SMEs, policymakers, and ecosystem actors in developing capacity-building frameworks and supportive policies to foster sustainable digital transformation.